2009
DOI: 10.1115/1.3135198
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Wireless Power on Medical Device Design Safety

Abstract: Wireless power holds great promise for solving many power distribution problems. Medical device designers will need to understand the impact of the electromagnetic coupling used for wireless power systems to design safe electromagnetic environments and safe medical devices. One question for designers will be whether or not current standards and requirements used for testing the electromagnetic compatibility (EMC) of medical devices and human exposure go far enough to insure safe environments and safe and relia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Previous works have shown that wireless electromagnetic energy transfer through induction, radio frequency waves, or resonant evanescent coupling results in thermal effects on tissues [ 8 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. The temperature of a wireless power receiver will rise as the energy is being transferred.…”
Section: Motivation and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous works have shown that wireless electromagnetic energy transfer through induction, radio frequency waves, or resonant evanescent coupling results in thermal effects on tissues [ 8 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. The temperature of a wireless power receiver will rise as the energy is being transferred.…”
Section: Motivation and Problem Statementmentioning
confidence: 99%
“…Wireless charging can result in more serious thermal effects [ 26 , 27 , 28 ]. Wireless energy transfer can result in thermal effects on tissues is stated in many works [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 29 ]. The temperature of a wireless power receiver will rise as the energy is being transferred.…”
Section: Related Workmentioning
confidence: 99%